PENGARUH ROA, EPS, DAN DER TERHADAP RETURN SAHAM (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023) - Gusdianto, Tedi; Priscilla Uning; Dian Noor Citra Perdana (ITB AAS Indonesia Surakarta, 2025)
This research aims to determine the effect of Return On Assets (ROA), Earning Per Share (EPS), and Debt to Equity Ratio (DER) to Stock Return on Coal Mining Companies listed in Indonesia Stock Exchange 2021-2023 period either partially or simultaneously.This research is an causality research. The population in this research are coal mining companies. The sampling selection used purposive sampling technique and obtained 86 research samples of financial statements of issuers. The data in this research was secondary data obtained from Indonesia Stock Exchange (BEI).Â